Trust beneficiaries and third parties - Follan, Patrick J. (The University of Edinburgh, 2021)
This thesis is about the juridical nature of the beneficiary’s right in a Scottish trust. Its central contention is that the beneficiary holds no more than a personal right against the trustee. The focus of the discussion is on the compatibility of this view with two important - and apparently more than merely personal - effects produced by the trust in relation to third parties. The first is the capacity of the beneficiary to proceed against a third party transferee of trust property taking in breach of trust or breach of fiduciary duty, or against a third party who has otherwise incurred an obligation to the trust. The second is the entitlement of the beneficiary to trust property on the insolvency of the trustee in preference to that trustee’s personal creditors. The thesis demonstrates that, while these effects on third parties have often led to the characterisation of the beneficiary’s right as either real or more than personal in nature, both the liability of third parties and the protection of trust property from creditors are explicable if the right is conceptualised as a personal right against the trustee. In relation to a beneficiary’s capacity to proceed against a third party taking trust property in breach of trust, the thesis contends that the beneficiary’s action arises not from any right in the trust property but rather from the application in the context of trust law of a body of rules which allow for the setting aside of a transaction in fraud of a creditor. In combination with statutory restrictions, this approach serves to determine the limits of a beneficiary's claim against a party taking in breach of trust. The same body of rules which explain claims for breach of trust may also, it is argued, be extended to account for the liability to the beneficiary of a transferee taking in breach of a trustee’s fiduciary duty. By contrast, the ability of a beneficiary to proceed against a third party who has incurred an obligation to the trust arises from a procedural rule representing an exception to the principle that the trustee alone is entitled to pursue claims against such third parties. The rule that trust property enjoys protection from the personal creditors of the trustee has a long history in Scots law involving, in particular, a number of changes of underlying rationale. The thesis shows how the protection of trust property was originally predicated upon the vulnerability of a creditor to the personal right of the beneficiary against a debtor trustee. That approach resulted in differences in protection from creditors between different forms of property as well as between latent and patent trusts. Protection was then extended to all forms of trust property in trusts of any kind on the basis of a view of the beneficiary as holding a right in the trust property. This rule, but not its underlying rationale, was preserved in the late 20th century with the coming of a patrimonial approach to the trust. That approach, it is argued, provides the most appropriate basis for the protection of trust property from creditors.
Keywords: trusts; beneficiary; personal right; property in trust; protection from creditors